Social Reliability in Qualitative Team Research - Sanders, Carrie B.; Cuneo, Carl J. (Sociology (Oxford), 2010)
Much of the attention in team-based qualitative research has been on reflexivity, subjectivity, and emotionality in the relationships between researchers and subjects during data collection and analysis. There has been less emphasis on the relationships among researchers, especially the social dynamics of inter-coder agreement in what we call in this article 'social reliability'. We explore three aspects of social reliability during team coding: explicit team knowledge, implicit team suppositions and assumptions, and explicit and implicit emotionality. Inter-coder reliability is not merely a methodological and scientific issue, but also a social one. Researchers ignore it at their peril. We suggest that researchers should endeavour to develop ways of explicitly recognizing and incorporating social reliability into their projects in order to enrich our understanding of research subjects.